Hippocampal volume and total cell numbers in major depressive disorder - Cobb, Justin A. (2012)
Neuroimaging consistently reveals smaller hippocampal volume in recurrent or chronic major depressive disorder (MDD). The underlying cellular correlates of the smaller volume are not clearly known. Postmortem tissues from 17 pairs of depressed and control subjects were obtained at autopsy, and informant-based retrospective psychiatric assessment was performed. Formalin-fixed left temporal lobes were sectioned (40 μm), stained for Nissl substance, and every 60(th) section selected throughout the entire hippocampus. Total volume of the hippocampal formation was calculated, and total numbers of pyramidal neurons (in hippocampal fields CA1, CA2/3, hilus), dentate gyrus (DG) granule cells, and glial cells were estimated stereologically. While hippocampal volume in all MDD subjects was not significantly smaller versus control subjects, in recurrent/chronic MDD, total volume decreased with duration of depressive illness (r=−0.696, p<0.026). There was no significant difference between MDD and controls in total number or density of pyramidal neurons/granule cells or glial cells in CA1, CA2/3, hilus, or DG. However, CA1 pyramidal neuron density increased with duration of illness in recurrent/chronic MDD (r=0.840, p<0.002). Granule cell (r=0.971, p<0.002) and glial cell numbers (r=0.980, p<0.001) increased with age in those taking antidepressant medication (n=6). Increasing DG granule cell and glial cell numbers with age in antidepressant-treated subjects may reflect proliferative effects of antidepressant medications. Decreasing total volume and increasing CA1 pyramidal neuron density with duration of illness in recurrent/chronic MDD lends support to the neuropil hypothesis of MDD.